Simulated ward round: reducing costs, not outcomes. (1st March 2016) - Ford, Helen; Cleland, Jennifer; Thomas, Ian
Summary: Background: Distractions and interruptions on the ward pose substantial patient safety risks, but medical students receive little training on their management. Although there is some evidence that medical students can be taught how to manage distractions and interruptions in a simulated ward environment, the only model to date is based on individual feedback, which is resource‐expensive, mitigating curricular integration. Our aim was to assess the educational utility of a cost‐efficient approach to a patient safety‐focused simulated ward round. Methods: Twenty‐three of 55 final‐year medical students took part in a cost‐reduced simulated ward round. Costs were minimised by providing group rather than individualised feedback, thereby shortening the duration of each simulation and reducing the number of interruptions. The utility of the simulation was assessed via student evaluation and performance on a patient safety station of an objective structured clinical examination (OSCE). Findings: The direct costs of the simulation were more than 50 per cent lower per student compared with the original study, mostly as a result of a reduction in the time that faculty members took to give feedback. Students managed distractions better and received higher scores in the OSCE station than those who had not undergone the ward round. Group feedback was evaluated positively by most participants: 94 per cent of those who provided feedback agreed or strongly agreed that the simulation would make them a safer doctor and would improve their handling of distractions. Our aim was to assess the educational utility of a cost‐efficient approach to a patient safety‐focused simulated ward round Discussion: The costs of a simulated ward round can be significantly reduced whilst maintaining educational utility. These findings should encourage medical schools to integrate ward simulation into curricula.